2020
DOI: 10.3390/ani10040595
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Interactions in Search and Rescue Dogs and Their Handlers

Abstract: Search and rescue dogs are an important link in the search for missing persons. The aim of the study was to assess exam stress in search and rescue dogs and their handlers. The study included 41 rescue teams taking exams of field and rubble specialties. The level of cortisol, which is the main glucocorticosteroid modulating stress reactions in humans and dogs, was analyzed. The biological material used to assess the hormone concentration was saliva collected in a non-invasive way. In total, 164 test samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Surprisingly, the handlers did not significantly increase their HR compared to baseline when climbing above 2100 m.a.s.l. Few authors have studied the synchronization between dog and human physiological parameters [ 16 , 17 , 18 , 20 ]. These previous works mainly evaluated the human–dog correlations of hormone levels concerning changes in emotional states [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the handlers did not significantly increase their HR compared to baseline when climbing above 2100 m.a.s.l. Few authors have studied the synchronization between dog and human physiological parameters [ 16 , 17 , 18 , 20 ]. These previous works mainly evaluated the human–dog correlations of hormone levels concerning changes in emotional states [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have studied the synchronization between dog and human physiological parameters [ 16 , 17 , 18 , 20 ]. These previous works mainly evaluated the human–dog correlations of hormone levels concerning changes in emotional states [ 17 , 18 ]. Recently, Carballo et al [ 41 ] demonstrated that handler stress influenced not only the behavior but also the HR of working dogs during search and rescue tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the occurrence of stress in horses, the concentration of pituitary–adrenal axis hormones determined in saliva is increasingly used [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Non-invasive methods for assessment of stress response increasing, e.g., the level of free transcortin-unbound cortisol [ 9 , 10 , 11 ], are used in other animal species as well [ 12 , 13 , 14 , 15 , 16 ]. Such biological material is sampled with no additional pain, stress, or discomfort and the material can be collected by non-veterinarians [ 9 , 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the setting and goals of AAI and voluntary canine search and rescue deployment are significantly different, these results suggest that the presence of canines can have a beneficial effect on PTSD. Additionally, there appears to be a strong interaction between the stress levels of dogs and their handlers [ 29 ]. Taken together, both findings highlight the particularities of voluntary dog handlers, as opposed to other rescue workers, and emphasize the necessity of taking a closer look at this particular subgroup.…”
Section: Introductionmentioning
confidence: 99%